1946
DOI: 10.1021/jo01175a015
|View full text |Cite
|
Sign up to set email alerts
|

CHEMICAL REACTIONS OF THE NITROGEN MUSTARD GASES.1 I. THE TRANSFORMATIONS OF METHYL-BIS(β-CHLOROETHYL)AMINE IN WATER

Abstract: This work was done in whole under Contract No. OEMsr-313 between The Rockefeller Institute for Medical Research and the Office of Scientific Research and Development, which assumes no responsibility for the accuracy of the statements contained herein. The experiments were performed during the period June 1942-January 1944

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

1949
1949
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(55 citation statements)
references
References 7 publications
2
53
0
Order By: Relevance
“…Should the rings have been opened by carbon disulfide, the C-H stretching frequencies would be expected at lower energies. Since there are no N-H bonds in products 1 and 2, as there are in the parent compounds and in 2-thiazolidinethione complexes, it is concluded that ~i ( a z ) , , ,~+ and Ni(meaz),,+ undergo carbon disulfide ~nsertion reactions [3] to provide dithiocarbamates as has been reported previously for other nickel(I1)-amine complexes (10).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Should the rings have been opened by carbon disulfide, the C-H stretching frequencies would be expected at lower energies. Since there are no N-H bonds in products 1 and 2, as there are in the parent compounds and in 2-thiazolidinethione complexes, it is concluded that ~i ( a z ) , , ,~+ and Ni(meaz),,+ undergo carbon disulfide ~nsertion reactions [3] to provide dithiocarbamates as has been reported previously for other nickel(I1)-amine complexes (10).…”
Section: Resultssupporting
confidence: 68%
“…H2C-S A similar reaction occurs with 2-methylaziridine (3,4), although it has been reported in the patent literature that dithiocarbamate salts can be obtained from 2-methylaziridine, carbon disulfide, and base (5,6 can be prepared directly from many amine complexes by carbon disulfide insertion reactions (7-lo), it was of interest to investigate the reaction of carbon disulfide with aziridines coordinated to a metal ion. We report here the results of these investigations and some tentative conclusions concerning the structure of the unusual compounds formed.…”
Section: H2c'mentioning
confidence: 99%
“…Aqueous solvolysis of these compounds has been abundantly shown to involve a reactive though isolable ethylenimonium ion intermediate, XCIII (44,52,53,150,271,283,284,306,323,572,573,574,625).…”
Section: Solvolyeie(b)mentioning
confidence: 99%
“…The pH of the solution was 8.6; undue polymerization was thus avoided. After storage at 30°or 37°for 24 hours over 90 per cent of the total chlorine was found to be in the ionic form when titrated with silver nitrate (Golombic, Fruton and Bergmann, 1946 (Peterson and Greenberg, 1952) Radioactive chromatogramn, were exposed to Ilfex film.…”
Section: Methodsmentioning
confidence: 99%